Induction of oxazolone-mediated features of atopic dermatitis in NOD-scid IL2Rγnull mice engrafted with human peripheral blood mononuclear cells - Thomas Nolte; Maryam Zadeh-Khorasani; Orkhan Safarov; Franziska Rueff; Rita Varga; Nadja Herbach; Rüdiger Wanke; Andreas Wollenberg; Thomas Mueller; Roswitha Gropp; Eckhard Wolf; Matthias Siebeck (The Company of Biologists, 2013)
SUMMARY Animal models mimicking human diseases have been used extensively to study the pathogenesis of autoimmune diseases and the efficacy of potential therapeutics. They are, however, limited with regard to their similarity to the human disease and cannot be used if the antagonist and its cognate receptor require high similarity in structure or binding. Here, we examine the induction of oxazolone-mediated features of atopic dermatitis (AD) in NOD-scid IL2Rγnull mice engrafted with human peripheral blood mononuclear cells (PBMC). The mice developed the same symptoms as immunocompetent BALB/c mice. Histological alterations induced by oxazolone were characterized by keratosis, epithelial hyperplasia and influx of inflammatory cells into the dermis and epidermis. The cellular infiltrate was identified as human leukocytes, with T cells being the major constituent. In addition, oxazolone increased human serum IgE levels. The response, however, required the engraftment of PBMC derived from patients suffering from AD, which suggests that this model reflects the immunological status of the donor. Taken together, the model described here has the potential to evaluate the efficacy of therapeutics targeting human lymphocytes in vivo and, in addition, might be developed further to elucidate molecular mechanisms inducing and sustaining flares of the disease.